Enhanced Fluoride Adsorption on Aluminum-Impregnated Kenaf Biochar: Adsorption Characteristics and Mechanism - Choi, Moon Yeong; Lee, Chang Gu; Park, Seong Jik (Water, Air, and Soil Pollution, 2022)
In this study, kenaf, a fast-growing plant, was pyrolyzed to biochar, and the biochar was impregnated with aluminum to improve its fluoride adsorption capacity. The Al-impregnated kenaf biochar (Al-KNF-BC) was pyrolyzed at temperatures of 300–700 °C, where the specimen treated at 300 °C (Al-KNF-300) demonstrated the highest fluoride adsorption capacity. The kinetics and equilibrium adsorption of fluoride by Al-KNF-300 followed the pseudo-second-order and Langmuir models, respectively. According to the Langmuir model, the maximum fluoride adsorption capacity of Al-KNF-300 was 13.93 mg/g. The enthalpy and entropy of fluoride adsorption by Al-KNF-300 were 37.80 kJ/mol and 124.1 J/mol K, respectively. Fluoride adsorption by Al-KNF-300 was favorable at pH values as low as 3, and the effect of anion competition followed the order HCO3− > SO42− > NO3− > Cl−. A maximum adsorption efficiency of 99.23% was obtained at an adsorbent concentration of 16.67 g/L, at which point the fluoride concentration decreased from 100 to < 1.5 mg/L (the drinking water standard). Based on these results, Al-KNF-300 can be considered an effective and inexpensive adsorbent for removing fluoride from contaminated water to meet drinking water standards.
Keywords: Adsorption capacities; Adsorption characteristic; Adsorption mechanism; Al-based adsorbent; Biochar; Drinking water standards; Fluoride adsorptions; Fluoride removal; Kenaf; Langmuir models; Al-based adsorbents; Biochar; Fluoride removal; Impregnation; Kenaf